Comparison of modified vacuum dressing and wet normal saline dressing in treatment of non-healing diabetic foot ulcers - Muneer, Muhammed; Thomas, Thomas K.; Babu, Dayananda; Paul, Deepak (International Surgery Journal, 2019)
Background: Diabetic foot a complication of diabetes can lead to significant morbidity and have financial burden. The standard of dressing diabetic foot ulcers has been saline dressings. Negative pressure vacuum devices have come and had a significant impact on treatment of diabetic ulcers. But in developing countries the cost associated with it makes it inaccessible to a large population. Our study aims to compare the use of modified vacuum dressing against saline dressing and compare healing rates, costs involved and hospital stay of patients. Methods: Our study was prospective study of 80 patients randomised into two groups, of 40 each. Group A consisted of patients with modified vacuum dressing and group B with wet saline dressing. Simple randomisation technique was used. They were compared for healing rates, hospital stay and cost involved. Results: There was a 43.75% decrease in area of the ulcer in group A compared to 25.15% in group B after 4 weeks. Decrease in wound depth was 55.41% and 26.94% in group A and B respectively. The mean hospital stay was 33.18 days in group A compared to 45.58 days in group B. The average cost incurred for patients in group A was rupees 14,381 compared to 19,465 rupees in group B. Conclusions: From our study we found that modified vacuum dressing in spite of being cheap it reduces healing time, hospital stay there by the cost incurred to patients. So we recommended modified vacuum dressings as a go to method of treating diabetic foot ulcers.